2002
DOI: 10.1007/s00421-002-0612-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training and/or fish oil supplemented diet on cytoplasmic fatty acid binding protein in rat skeletal muscles and heart

Abstract: Endurance training and/or a fish oil supplemented diet affect cytoplasmic fatty acid binding protein (FABP(c)) content in rat skeletal muscles and heart. After 8 weeks of swimming, trained rats exhibited higher FABP(c) content in the extensor digitorum longus (EDL) and in the gastrocnemius than did control rats (30%). The FABP(c) increase was associated with an increase of citrate synthase activity (85% and 93%, respectively, in the two muscles), whereas lactate dehydrogenase activity decreased significantly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 43 publications
(57 reference statements)
1
29
0
1
Order By: Relevance
“…However, these findings are difficult to extrapolate to human insulin resistance because complete genetic H-FABP deficiencies have not been reported. In humans, levels of H-FABP vary in response to numerous physiological and pathological states associated with altered rates of LCFA flux, including chronic exercise training (8), diets supplemented with (-3) polyunsaturated LCFA (9), and weight loss (10). These studies clearly show levels of H-FABP to be dynamic and to fluctuate with LCFA demands.…”
mentioning
confidence: 91%
“…However, these findings are difficult to extrapolate to human insulin resistance because complete genetic H-FABP deficiencies have not been reported. In humans, levels of H-FABP vary in response to numerous physiological and pathological states associated with altered rates of LCFA flux, including chronic exercise training (8), diets supplemented with (-3) polyunsaturated LCFA (9), and weight loss (10). These studies clearly show levels of H-FABP to be dynamic and to fluctuate with LCFA demands.…”
mentioning
confidence: 91%
“…A study by Chang et al indicated that vitamin E influences the training-induced adaptation of glutathione peroxidase (GPX) and superoxide dismutase (SOD) activities in rat skeletal muscle (11); in rats, the deprivation of vitamin E increased the exercise-induced elevation in GPX activity and inhibited exercise-induced SOD activity (14). A study conducted by Baumgartner et al showed that mild oxidative stress led to activation of the intrinsic pathway of apoptosis and death in skeletal muscle cells, which was reduced by supplementation of the culture medium with vitamin E (26).…”
Section: Vitamin E Maintains Skeletal Muscle Which May Slow Down the mentioning
confidence: 99%
“…Various theories on the pathology of osteoarthritis are being investigated that may lead to new therapeutic options. These relate to the role of skeletal muscle (11)(12)(13)(14), the effect of nucleic acid metabolism (15,16), sex gland functions (17)(18)(19), the action of stable mast cells (20,21) and the importance of the subchondral vascular system (9,22,23) in osteoarthritis and its progression. In the present review, the possibility that vitamin E may be able to delay the progression of osteoarthritis was explored through studying the potential role of this nutritional factor in each of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Endurance training and/or a fish-oil-supplemented diet can affect cytoplasmic fatty-acid-binding protein (FABP[c]) content in rat skeletal muscles and heart (Clavel, Farout, Briand, Briand, & Jouanel, 2002). After 8 weeks of swimming, 34 trained rats exhibited higher FABP(c) content in the extensor digitorum longus and in the gastrocnemius than did the 32 control rats.…”
Section: Omega-3 Fatty Acids and Exercise Metabolismmentioning
confidence: 99%
“…As a result, both exercise and the omega-3 PUFA-enriched diet influenced FABP(c) content in muscle. These two physiological treatments presumably acted on FABP(c) content by increasing fatty-acid flux within the cell (Clavel et al, 2002). The shift toward a greater use of fat reduces the rate of glycogen depletion and thus fatigue.…”
Section: Omega-3 Fatty Acids and Exercise Metabolismmentioning
confidence: 99%